Systemic coordination of whole-body tissue remodeling during local regeneration in sea anemones - Cheung, Stephanie; Bredikhin, Danila; Gerber, Tobias; Steenbergen, Petrus J.; Basu, Soham; Bailleul, Richard; Hansen, Pauline; Paix, Alexandre; Benton, Matthew A.; Korswagen, Hendrik C.; Arendt, Detlev; Stegle, Oliver; et al. (Developmental cell, 2025)
The complexity of regeneration extends beyond local wound responses, eliciting systemic processes across the entire organism. However, the functional relevance and coordination of distant molecular processes remain unclear. In the cnidarian Nematostella vectensis, we show that local regeneration triggers a systemic homeostatic response, leading to coordinated whole-body remodeling. Leveraging spatial transcriptomics, endogenous protein tagging, and live imaging, we comprehensively dissect this systemic response at the organismal scale. We identify proteolysis as a critical process driven by both local and systemic upregulation of metalloproteases. We show that metalloproteinase expression levels and activity scale with the extent of tissue loss. This proportional response drives long-range tissue and extracellular matrix movement. Our findings demonstrate the adaptive nature of the systematic response in regeneration, enabling the organism to maintain shape homeostasis while coping with a wide range of injuries.